2020
DOI: 10.1093/imanum/drz075
|View full text |Cite
|
Sign up to set email alerts
|

Localized inverse factorization

Abstract: We propose a localized divide and conquer algorithm for inverse factorization S −1 = ZZ * of Hermitian positive definite matrices S with localized structure, e.g. exponential decay with respect to some given distance function on the index set of S. The algorithm is a reformulation of recursive inverse factorization [J. Chem. Phys., 128 (2008), 104105] but makes use of localized operations only. At each level of recursion, the problem is cut into two subproblems and their solutions are combined using iterative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 53 publications
(101 reference statements)
0
12
0
Order By: Relevance
“…Then, I − Z * 0 SZ 0 2 < 1, which implies convergence of iterative refinement with Z 0 as starting guess [23]. This result was recently strengthened and it was shown that [22]. Those convergence results immediately suggest a recursive inverse factorization algorithm where iterative refinement is combined with a recursive binary principal submatrix decomposition of the matrix S.…”
Section: Recursive and Localized Inverse Factorizationmentioning
confidence: 92%
See 3 more Smart Citations
“…Then, I − Z * 0 SZ 0 2 < 1, which implies convergence of iterative refinement with Z 0 as starting guess [23]. This result was recently strengthened and it was shown that [22]. Those convergence results immediately suggest a recursive inverse factorization algorithm where iterative refinement is combined with a recursive binary principal submatrix decomposition of the matrix S.…”
Section: Recursive and Localized Inverse Factorizationmentioning
confidence: 92%
“…In order to minimize the number of parameters, we employ the automatic stopping criterion proposed in [18] and used in [22]. The iterative refinement is stopped as soon as δ i+1 F > δ i m+1 F .…”
Section: Iterative Refinementmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of factorization has been found useful not only in general parallel iterative solvers but also in solving generalized eigenvalue problems that arise from computation of electronic structures. See, for example, [6], [7] and the recent survey [14].…”
Section: Introductionmentioning
confidence: 99%